2022
DOI: 10.3389/fcimb.2022.939532
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral malaria induced by plasmodium falciparum: clinical features, pathogenesis, diagnosis, and treatment

Abstract: Cerebral malaria (CM) caused by Plasmodium falciparum is a fatal neurological complication of malaria, resulting in coma and death, and even survivors may suffer long-term neurological sequelae. In sub-Saharan Africa, CM occurs mainly in children under five years of age. Although intravenous artesunate is considered the preferred treatment for CM, the clinical efficacy is still far from satisfactory. The neurological damage induced by CM is irreversible and lethal, and it is therefore of great significance to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 145 publications
0
31
0
1
Order By: Relevance
“…[29][30] Several studies showed that malaria infection triggers long-term neurological deficits such as neurobehavioral disorders, motor skills, visual acuity, and seizures. [31][32] This study demonstrated that the administration of curcumin and kaempferol could suppress the development of ECM in mice by reducing the breakdown of the BBB and the neurobehavioral disorders associated with the disease. Several studies also reported strong antioxidant and anti-inflammatory activities that can produce a protective effect in the brains of PbA-infected mice.…”
Section: Groupsmentioning
confidence: 88%
“…[29][30] Several studies showed that malaria infection triggers long-term neurological deficits such as neurobehavioral disorders, motor skills, visual acuity, and seizures. [31][32] This study demonstrated that the administration of curcumin and kaempferol could suppress the development of ECM in mice by reducing the breakdown of the BBB and the neurobehavioral disorders associated with the disease. Several studies also reported strong antioxidant and anti-inflammatory activities that can produce a protective effect in the brains of PbA-infected mice.…”
Section: Groupsmentioning
confidence: 88%
“…A more pronounced coma was previously described as a risk factor for death during severe malaria in children [ 28 ], in adults presenting with CM [ 29 ], and in children presenting with CM [ 30 , 31 ]. Splenomegaly is also a clinical manifestation classically described in cerebral malaria [ 32 , 33 ], although rarely identified as a risk factor for death during CM. Through the analysis of haematologic factors, we observed higher numbers of leukocytes, among which lymphocytes and monocytes were associated with CM death, indicating an increased immune response related to the infection.…”
Section: Discussionmentioning
confidence: 99%
“…[28], in adults presenting with CM [29], and in children presenting with CM [30,31]. Splenomegaly is also a clinical manifestation classically described in cerebral malaria [32,33], although rarely identi ed as a risk factor for death during CM. Through the analysis of haematologic factors, we observed higher numbers of leukocytes, among which lymphocytes and monocytes were associated with CM death, indicating an increased immune response related to the infection.…”
Section: Discussionmentioning
confidence: 99%